1996
DOI: 10.2351/1.4745429
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser interactions with an aluminum alloy

Abstract: An AlCuMg alloy was irradiated using a KrF pulsed excimer laser. A microstructural study showed the presence of a laser treated zone having a uniform depth of approximately 20 μm. The surface layer of the laser treated aluminum alloy exhibited a wavy topography and its surface roughness was found to depend on the number of laser pulses per step. A X-ray diffraction analysis revealed the presence of aluminum oxides and nitrides on the surface of the laser irradiated specimens. Corrosion measurements showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the second regime the layer solidified with a fine cellular structure, growing upwards-parallel to the thermal gradient, which coarsens with the layer thickness. To date, layers below this thickness have been reported as being 'homogeneous', which has been linked to a substantial improvement in corrosion resistance [3,[5][6][7][8][11][12][13][14][15]. To prevent the formation of a cellular structure throughout the layer on resolidification, and ensure a reasonable chance of obtaining a chemically homogeneous layer, the melt depth is thus restricted to less than ∼10 m in thickness.…”
Section: Solidification Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second regime the layer solidified with a fine cellular structure, growing upwards-parallel to the thermal gradient, which coarsens with the layer thickness. To date, layers below this thickness have been reported as being 'homogeneous', which has been linked to a substantial improvement in corrosion resistance [3,[5][6][7][8][11][12][13][14][15]. To prevent the formation of a cellular structure throughout the layer on resolidification, and ensure a reasonable chance of obtaining a chemically homogeneous layer, the melt depth is thus restricted to less than ∼10 m in thickness.…”
Section: Solidification Conditionsmentioning
confidence: 99%
“…Recently, several studies have been reported demonstrating dramatic improvements in corrosion performance that can be gained from pulsed laser surface treatments of aluminium alloys and welds made in aerospace materials [3,[5][6][7][8][11][12][13][14][15]. In all of these publications emphasis has been placed upon characterisation of the treated surfaces improved corrosion behaviour, with less attention paid to the microstructural changes in the subsurface layer that underpin these changes.…”
Section: Introductionmentioning
confidence: 99%
“…47 Few investigations are carried out on laser nitriding of aluminium alloys in solid state. [48][49][50] Laser nitriding of aluminium alloys in liquid state was investigated by Bergmann and co-workers. [51][52][53][54] They produced by laser gas nitriding on technical alloys crack free, dense, AlN containing gradient surface layers with a thickness up to 20 mm.…”
Section: Laser Gas Alloying Of Titanium and Aluminium Alloys: Laser N...mentioning
confidence: 99%
“…With the extremely short pulse duration (typically ,20 ns) and high energy per photon of the excimer lasers, some remarkable surface modifications can take place. In fact, Al 2 O 3 and AlN phases 7 in the form of adhered films were detected in the resolidified surface layer of aluminium alloys after excimer laser treatment in a nitrogen environment. 8 However, the structure of the surface film has not been studied in detail and its effect on corrosion properties has not been unequivocally determined.…”
Section: Introductionmentioning
confidence: 99%